Assessment of quality of life in diabetes and hypertensive patients attending tertiary care hospitals in (Jammu), (Jammu and Kashmir) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The numbers of individuals with chronic conditions, particularly those with hypertension and diabetes, have a low Quality of Life as a result of their treatment and lifestyle choices. It can also cause a slew of difficulties in the body's systems, as well as unfavourable metabolic circumstances that impair one's quality of life. The goal of this study is to find out how satisfaction with hypertension affects quality of life in people with hypertension and diabetes. A six-month prospective cross-sectional study was carried out in a tertiary care facility in (District) (State). A total of 200 patients were consented to be interviewed in order to gather information on socio demographics, physical, mental, and behavioural characteristics using a standardised questionnaire. The MINICHAL scale, which has 17 questions and is divided into two domains, mental domain and somatic domain, is used to assess quality of life. It has four possible replies, with scores of 0=not at all, 1=yes, somewhat, 2=yes, a lot, and 3=yes, a lot, with a total of points ranging from 0-51. The greatest and worst levels of health are indicated by the International Diabetes Federation, while the last question is a sign of the patient's general agreement to participate in the survey. According to the findings of this study, the average quality of life in hypertension is 61.83 percent, and the average quality of life in hypertension and diabetes is 42.22 percent. Using the chi square test, a significant association was also discovered, with a p value of 0.001. This learning presentation demonstrates that self-care is important to avoid disease, and that, based on historical comments; more counselling is required in patients to improve their Quality of Life.